2018
DOI: 10.1016/j.juro.2018.03.115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Management of Testosterone Deficiency: AUA Guideline

Abstract: The care of testosterone deficient patients should focus on accurate assessment of total testosterone levels, symptoms, and signs as well as proper on-treatment monitoring to ensure therapeutic testosterone levels are reached and symptoms are ameliorated. Future longitudinal observational studies and clinical trials of significant duration in this space will improve diagnostic techniques and treatment of men with testosterone deficiency as well as provide more data on the adverse events that may be associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
652
0
26

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 525 publications
(684 citation statements)
references
References 46 publications
6
652
0
26
Order By: Relevance
“…injections and s.c. pellets. The AUA, AACE, BSSM, and ISSM recommend against oral 17α alkylated testosterone because it can lead to hepatotoxicity . The AUA, EAU, BSSM, and AACE all recognise the risk of transference with topical TTh (Table ) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…injections and s.c. pellets. The AUA, AACE, BSSM, and ISSM recommend against oral 17α alkylated testosterone because it can lead to hepatotoxicity . The AUA, EAU, BSSM, and AACE all recognise the risk of transference with topical TTh (Table ) .…”
Section: Methodsmentioning
confidence: 99%
“…However, there is concern in the literature that TTh can increase risk of major adverse cardiovascular events (MACE), such as MI or cerebrovascular accident. All guideline committees either comment that there is insufficient data in the literature that TTh increases the risk of MACE, or acknowledge the conflicting data (Table ) . Per the AUA guidelines, TTh should not be given to patients who have had a MI or stroke within the past 3–6 months .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One reason for this increased risk is that the viscosity of blood in KS patients is high, causing the formation of venous thromboembolism . In addition, Campbell et al found that the risks of pulmonary embolism and deep venous thrombosis were 5‐20 times higher in KS patients than in normal healthy men . The updated AUA guideline for the evaluation and management of testosterone deficiency indicates that whether TRT increases or decreases the risk of cardiovascular events cannot be definitively stated.…”
Section: Postinfertility Management: Diagnosis Of Ks Is a Proxy Of Gementioning
confidence: 99%